Simulation Methods for Reliability and Availability of Complex Systems - Faulin, Javier; Juan, Angel A.; Martorell Alsina, Sebastián Salvador; Ramirez-Marquez, Jose Emmanuel (Springer Series in Reliability Engineering, 2010)
Complex systems have become ubiquitous and are essential to today's society. The design of reliable complex systems and the determination of their availability are therefore very important tasks for managers and engineers. These tasks, however, can be extremely difficult to achieve, due to the fact that current analytical methods are often too complicated, time-consuming, inefficient, or even inappropriate, when dealing with real-life systems. Simulation Methods for Reliability and Availability of Complex Systems discusses the use of computer simulation-based techniques and algorithms to determine reliability and availability (R&A) levels in complex systems, and to support the improvement of these levels both at the design stage and during the system operating stage. It presents current best practice in the field, as well as: • sharing theoretical or applied models and decision support systems that make use of simulation to estimate and to improve system R&A levels; • forecasting emerging technologies and trends in the use of computer simulation for R&A; and • proposing hybrid approaches to the development of efficient methodologies designed to solve R&A-related problems in real-life systems. Dealing with practical issues, Simulation Methods for Reliability and Availability of Complex Systems is designed to support managers and system engineers in the improvement of R&A, as well as providing a thorough exploration of the techniques and algorithms available for researchers, and for advanced undergraduate and postgraduate students. Springer Series in Reliability Engineering publishes high-quality books in important areas of current theoretical research and development in reliability, and in areas that bridge the gap between theory and application in areas of interest to practitioners in industry, laboratories, business, and government.